2018
DOI: 10.1097/md.0000000000012787
|View full text |Cite|
|
Sign up to set email alerts
|

SLICC damage index score in systemic lupus erythematosus patients and its associated factors

Abstract: The aims of this study were to determine damage index in systemic lupus erythematosus (SLE) patients based on Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) Damage Index (SDI) and to determine the laboratory and clinico-demographic factors affecting SDI.This is a retrospective cohort study of 94 SLE patients attending rheumatology clinics in 2 local hospitals in Kelantan, Malaysia. The patients were divided into 2 groups based on SDI score assigned by the attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Administrative data provide valuable real-world information; however, there are challenges when conducting this type of analysis. Certain aspects of healthcare patterns can be measured using administrative claims, such as inpatient admissions, ED visits, oral corticosteroid reduction and SLE flares using a proxy algorithm; however, the claims databases lack information on many of the patient-centric outcomes that are critical for the full evaluation of SLE, such as disease activity (eg, SLEDAI score,44 SLE Flare Index45), symptoms (eg, SLE severity, flares, fatigue), long-term organ damage (eg, the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index15 46) and the humanistic impact of the disease, including effects on HRQoL, productivity and functional status, and the impact on caregivers. As such, the results of this study must be interpreted within the context of the missing patient-centric outcomes data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administrative data provide valuable real-world information; however, there are challenges when conducting this type of analysis. Certain aspects of healthcare patterns can be measured using administrative claims, such as inpatient admissions, ED visits, oral corticosteroid reduction and SLE flares using a proxy algorithm; however, the claims databases lack information on many of the patient-centric outcomes that are critical for the full evaluation of SLE, such as disease activity (eg, SLEDAI score,44 SLE Flare Index45), symptoms (eg, SLE severity, flares, fatigue), long-term organ damage (eg, the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index15 46) and the humanistic impact of the disease, including effects on HRQoL, productivity and functional status, and the impact on caregivers. As such, the results of this study must be interpreted within the context of the missing patient-centric outcomes data.…”
Section: Discussionmentioning
confidence: 99%
“…SLE treatments include antimalarials, non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids and immunosuppressants 14. Due to persistent disease activity, a high proportion of patients require long-term corticosteroid and/or immunosuppressive treatment, which clinical studies suggest contributes to progressive organ damage accrual 15 16. On the basis of four phase 3 randomised trials,17–20 the safety and efficacy of intravenous and subcutaneous belimumab, a human IgG1λ monoclonal antibody against B-lymphocyte stimulator,21 has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…36 Some investigators have reported musculoskeletal system and neuropsychiatric as the most involved systems. 10,36 Damage accrual varies among ethnic groups, and damage in different systems does not follow a common pattern in SLE patients. [37][38][39][40] The prevalence of eye damage was lower in our cohort of patients in contrast to other studies, which reported them to be more than 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations into organ damage associated with SLE have typically compared patients according to the presence or absence of certain damage domains; alternatively they have investigated factors associated with damage accrual or the impact of damage on survival . Few studies have identified subphenotyes by identifying patterns of organ damage and relating them to organ damage, disease activity, mortality, and genetic background.…”
Section: Introductionmentioning
confidence: 99%